Latitudinal and seasonal plasticity in American bison Bison bison diets. (24th October 2020) - Hecker, Lee J.; Coogan, Sean C. P.; Nielsen, Scott E.; Edwards, Mark A.
Abstract: In ecological niche theory, diet is a trait frequently used to place species along a continuum from specialists to generalists. A multidimensional approach to investigating species' niches has been developed to incorporate nutrition. We apply the concepts of multidimensional nutritional niche theory to the dietary patterns of a widespread, large herbivore, the American bison Bison bison, at various levels of its nutritional niche. Specifically, we sought to estimate dietary niches for female bison at the levels of the forage items they consume and the macronutrients they acquire from those forage items. We assessed how these dietary niches changed seasonally and explored physical and climatic mechanisms that contribute to observed differences in the dietary niches. We also examined dietary differences between the two bison subspecies: wood bison Bison bison athabascae and plains bison Bison bison bison . We compiled data for 16 bison subpopulations using 26 peer‐reviewed publications, government reports, conference proceedings, and graduate theses that described the dietary composition of female bison for analysis of dietary niches. We found that the diets of female bison were, as expected, dominated by graminoids throughout the year, but during the growing season (spring and summer), dietary niches had greater breadth. Their diets were relatively high in carbohydrates, but percentages of dietary lipid and protein increased during the growing season. Further, we found significant increases in consumption of browse items, lipids, and proteins with increasing latitude (†N), and differences between American bison subspecies. Our study provides insight into the fundamental macronutrient niche of the American bison and also provides a framework for the nutritional targets of bison. We show that bison are able to adapt to availability of local forage and that they may consume different items in different proportions in order to regulate nutritional composition of their diet. Abstract : A right‐angled mixture triangle (RMT) that describes the macronutrient space America bison Bison bison occupy during the vegetative growing season (April–September; red) and during the non‐growing season (January–March; blue). We reviewed the diets of 16 bison herds across North America. Each number refers to a bison herd, with 1 being the most northern herd and 16 being the most southern herd. The RMT shows that during the growing season the estimated fundamental dietary niche (polygon) is 2.8 times greater in area than during the non‐growing season. Our results also indicated that bison at higher latitudes had significantly more lipids, which were correlated with browse items, in their diets.